Cultural Acculturation in Tourist Villages Against the Yogyakarta Prawirotaman Community - Adi Kara Prabowo; Ari Retno Purwanti (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Cultural acculturation can cause various forms of change and impact on society. The aim of this study. First, to analyze the process of cultural acculturation in the tourist village of Prawirotaman towards the community. Second, to find out the impact of cultural acculturation that has occurred on the people in the Prawirotaman tourist village. This study uses a qualitative method. This research was conducted in Prawirotaman Village, Brontokusuman Village, Mergangsan Kemantren from January to March 2023. Data collection techniques were carried out by interviews, observation and documentation to obtain the desired data. The number of research subjects is 7 (seven) people. Data analysis techniques are carried out through data collection, data reduction, data analysis, and drawing conclusions. Checking the validity of the data was carried out using data triangulation techniques. Research result. First, the process of cultural acculturation in the tourist village of Prawirotaman towards the community is a) The change of the batik village into a tourist village. b) Traditional houses turned into inns, hotels, restaurants and cafes. c) Kromo Inggil language which changed to Indonesian and Javanese Ngoko. d) Reduced mutual respect. e) Indigenous culture and traditions are still maintained. Second, the impact is a) Increasing the economy in society. b) Marriage between natives and tourists. c) Changes in behavior towards society, d) Structural changes. e) The relationship between natives and tourists is very good.